PM2.5 in the Yangtze River Delta, China: Chemical compositions, seasonal variations, and regional pollution events. (April 2017) - Ming, Lili; Jin, Ling; Li, Jun; Fu, Pingqing; Yang, Wenyi; Liu, Di; Zhang, Gan; Wang, Zifa; Li, Xiangdong
Abstract: Fine particle (PM2.5 ) samples were collected simultaneously at three urban sites (Shanghai, Nanjing, and Hangzhou) and one rural site near Ningbo in the Yangtze River Delta (YRD) region, China, on a weekly basis from September 2013 to August 2014. In addition, high-frequency daily sampling was conducted in Shanghai and Nanjing for one month during each season. Severe regional PM2.5 pollution episodes were frequently observed in the YRD, with annual mean concentrations of 94.6 ± 55.9, 97.8 ± 40.5, 134 ± 54.3, and 94.0 ± 57.6 μg m −3 in Shanghai, Nanjing, Hangzhou, and Ningbo, respectively. The concentrations of PM2.5 and ambient trace metals at the four sites showed clear seasonal trends, with higher concentrations in winter and lower concentrations in summer. In Shanghai, similar seasonal patterns were found for organic carbon (OC), elemental carbon (EC), and water-soluble inorganic ions (K +, NH4 +, Cl −, NO3 −, and SO4 2- ). Air mass backward trajectory and potential source contribution function (PSCF) analyses implied that areas of central and northern China contributed significantly to the concentration and chemical compositions of PM2.5 in Shanghai during winter. Three heavy pollution events in Shanghai were observed during autumn and winter. The modelling results of the Nested Air Quality Prediction Modeling System (NAQPMS) showed the sources and transport of PM2.5 in the YRD during the three pollution processes. The contribution of secondary species (SOC, NH4 +, NO3 −, and SO4 2- ) in pollution event (PE) periods was much higher than in BPE (before pollution event) and APE (after pollution event) periods, suggesting the importance of secondary aerosol formation during the three pollution events. Furthermore, the bioavailability of Cu, and Zn in the wintertime PM2.5 samples from Shanghai was much higher during the pollution days than during the non-pollution days. Graphical abstract: Abstract : Secondary aerosol formation is important and the bioavailability of trace metals is much higher during the pollution events.